Innovation and technology transfer in Japan and Europe : industry-academic interactions - Phillips, Glyn O. (Routledge library editions. Business and economics in Asia ;, 2019)
This book, first published in 1989, compares, contrasts and evaluates the nature, scale and direction of industry-academic interactions in Britain and Japan: the conversion of academic discoveries into practical products. Japan shows its outstanding ability to translate scientific ideas into high technology products. Within this wider investigation, detailed consideration is given to the manner in which these interactions promote innovation and technology transfer. The information in this study provides a perspective against which decisions can be made about industry-education interaction arrangements, and much of this information is largely unavailable outside Japan.